Fumaric acid production by Rhizopus species from acid hydrolysate of oil palm empty fruit bunches. - Pairazamán-Quiroz, O.D. (2024)
The hemicellulosic fraction of lignocellulosic biomass is a very important material, due to the significant concentration of pentoses present in its composition and that can be used sustainably in biotechnological processes such as the production of fumaric acid. Research efforts are currently being promoted for the proper disposal and valorization of empty fruit bunches (EFB) from oil palm. In this work, seventeen Rhizopus species were evaluated in a fermentation medium with EFB hydrolyzate, without detoxification, as a carbon source for fumaric acid production. Rhizopus circicans 1475 and Rhizopus 3271 achieved productions of 5.65 g.L−1 and 5.25 g.L−1 of fumaric acid at 30 °C, 120 rpm for 96 h, respectively. The percentage of consumed sugars, mainly pentoses, was 24.88% and 34.02% for R. circicans 1475 and R 3271, respectively. Soy peptone and ammonium sulfate were evaluated as nitrogen sources, where soy peptone stimulated the formation of biomass pellets while ammonium sulfate produced mycelia and clamps.